The Status of Government Administration in the Sphere of Crisis Management - Czuryk, Małgorzata; Kaczmarek, Krzysztof; Włodyka, Ewa (PRAWO i WIĘŹ, 2026)
The status of the government administration in crisis management is determined by its legal and constitutional position, as well as its location at central and local levels. This allows for the comprehensive implementation of tasks and a response to threats. Local government administration operates within the voivodeship, where the voivode is responsible for crisis management. In municipalities and districts, these tasks are carried out by the local government. This paper uses a dogmatic-legal approach to analyse the legal regulations governing crisis management and indicate the role of government administration in this area. A literature review was also conducted to inform the analysis. To cite examples from other countries, the methodology was supplemented with elements of the comparative method.